Mid-term fertilisers and lime effect on grassland in the hilly-mountain region in Balkan - Vladimir Zornić; Vesna Đurović; Mirjana Petrović; Snežana Babić; Dalibor Tomić; Nedeljko Racić; Jasmina Milenković (Plant, Soil and Environment)
Although the effects of fertiliser addition and liming on semi-natural grassland productivity and biomass quality are well documented, less is known about how fertilisers change plant functional groups and mean ecological values. We researched the effects of liming (no lime and lime with 1 t/ha) and mineral fertilisers (control - no fertilisers, PK-P60K60, N20PK-N20P60K60, N80PK-N80P60K60, and N140PK-N140P60K60) for nine years on the Danthonia alpina Vest. grassland community. Based on Brown-Blanquet cover abundance, we calculated Shannon-Wiener evenness and abundance of plant functional groups (based on height, canopy structure, storage organs presence and flowering duration). We also researched Landolt's ecological indicator values for nutrients, moisture, reaction, light, and temperature. Results revealed that fertilisers stimulated tall species with longer flowering duration. Shannon-Wiener evenness in control was 0.45, and N20PK increased to 0.71 but significantly decreased in treatment N140PK (0.25). Mean Landolt ecological value for nutrients and moisture increased while temperature dropped. The coverage of legumes and Landolt indicator value for nutrients increased because of the lime application, while the lime had no effect on Shannon-Wiener evenness and abundance of functional groups. Greater Shannon-Wiener evenness in treatments of PK and N20PK is a prerequisite for resistance to the effects of extreme climate events.